2016
DOI: 10.1525/mp.2016.33.3.306
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repetition on Attention in Two-Part Counterpoint

Abstract: epetition and novelty are essential components of tonal music. Previous research suggests that the degree of repetitiveness of a line can determine its relative melodicity within a musical texture. Concordantly, musical accompaniments tend to be highly repetitive, probably facilitating listeners’ tendency to focus on and follow the melodic lines they support. With the aim of contributing to the unexplored area of the relationship between repetition and attention in polyphonic music listening, this paper presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…Based on the literature in the field of time psychology indicating that extremely predictable stimuli shorten felt duration whereas stimuli that increase expectations without leading to habituation lengthen felt duration, we hypothesized that pieces structured in brief and frequent repetitive melodic units, as well as the melodic units themselves, will feel shorter than less redundant pieces and melodies. The notion that attention to a (nonmusical) stimulus increases the latter's perceived duration (Matthews, 2015;Tse, 2010;Tse et al, 2004;Ulrich et al, 2006;Zakay, 1993), combined with Huron's (2013) habituation-fluency theory of musical repetition and previous findings that musical parts (formal sections or textural layers) consisting of brief repeating melodies tend to rapidly decrease the listeners' attention to those parts over time (Margulis, 2012;Taher et al, 2016), further supports this hypothesis. Additionally, assuming that participants are engaged with the music, pieces that avoid redundancy of musical material should allow for the formation of musical expectations without the kind of superfluous predictability associated with extremely reiterative events.…”
Section: Summary and Relation To Current Researchsupporting
confidence: 60%
“…Based on the literature in the field of time psychology indicating that extremely predictable stimuli shorten felt duration whereas stimuli that increase expectations without leading to habituation lengthen felt duration, we hypothesized that pieces structured in brief and frequent repetitive melodic units, as well as the melodic units themselves, will feel shorter than less redundant pieces and melodies. The notion that attention to a (nonmusical) stimulus increases the latter's perceived duration (Matthews, 2015;Tse, 2010;Tse et al, 2004;Ulrich et al, 2006;Zakay, 1993), combined with Huron's (2013) habituation-fluency theory of musical repetition and previous findings that musical parts (formal sections or textural layers) consisting of brief repeating melodies tend to rapidly decrease the listeners' attention to those parts over time (Margulis, 2012;Taher et al, 2016), further supports this hypothesis. Additionally, assuming that participants are engaged with the music, pieces that avoid redundancy of musical material should allow for the formation of musical expectations without the kind of superfluous predictability associated with extremely reiterative events.…”
Section: Summary and Relation To Current Researchsupporting
confidence: 60%
“…In these contexts, repetition engenders saliency by focusing attention on both what is at hand within an auditory scene as well as on the relationship of the present auditory event with those that have recently past. It is noteworthy here that Taher et al (2016) suggesting that when presented with tonal two-part contrapuntal textures, listeners are susceptible to a rapid type of habituation capable of guiding attention away from repeated motives in one voice and toward novel information in another after just a single repetition.…”
Section: Repetition In Music Listeningmentioning
confidence: 81%
“…While that study examined concrete behaviors taken in a real-world scenario (and is thus different to the rating measurements taken here in the lab), we argue they reflect the same phenomenon: changes in interest in, and engagement with, music as function of perceivable structure. It has been shown that the presence of repetition (which likely negatively correlates with the presence of change) in musical streams is associated with drops in listeners’ perception of the musical stream as being salient (Taher, Rusch, & McAdams, 2016). Here we suggest that, conversely, a listener's perception of change, associated with experiencing moments as salient, leads them to experience increases in curiosity about how the music will continue to unfold.…”
Section: Discussionmentioning
confidence: 99%